2020
DOI: 10.3390/ijerph17239087
|View full text |Cite
|
Sign up to set email alerts
|

Is It Possible to Find Something Positive in Being Confined Due to COVID-19? Implications for Well-Being

Abstract: In relation to COVID-19, little research has focused on the study of variables that affect well-being during this pandemic. The purpose of this research is twofold: (1) to find out if people experiencing a quarantine are able to appreciate any positive aspects of it, and to analyze how these responses are categorized and (2) to check if there are differences in levels of well-being according to these categories. There were 243 representative participants of the Spanish population according to sex, age, and edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…Targeted and acceptable health education programs will provide individuals with a good understanding of COVID-19 and help them have a good understanding of why they were quarantined and how it will work. Merino et al found that people in the intrinsic orientation group (meaning those who are taking advantage of confinement to enjoy being with the family, personal development, and so on) show higher levels of psychological well-being and subjective well-being ( 46 ). So reinforcing the sense of altruism and cultivating a conscious appreciation of the social and individual values will reduce the mental health effects and improve their compliance ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Targeted and acceptable health education programs will provide individuals with a good understanding of COVID-19 and help them have a good understanding of why they were quarantined and how it will work. Merino et al found that people in the intrinsic orientation group (meaning those who are taking advantage of confinement to enjoy being with the family, personal development, and so on) show higher levels of psychological well-being and subjective well-being ( 46 ). So reinforcing the sense of altruism and cultivating a conscious appreciation of the social and individual values will reduce the mental health effects and improve their compliance ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Jest to zgodne z dotychczasowymi doniesieniami, że emocje pozytywne pełnią ważne funkcje w procesie stresu i są związane ze skutecznym radzeniem sobie (Folkman, 2008). Aktualne doniesienia empiryczne wskazują, że ludzie są w stanie dostrzec pozytywne aspekty w funkcjonowaniu w rzeczywistości pandemicznej, przy czym pozytywy te dotyczą zarówno funkcjonowania w sferze rodzinnej, jak i społecznej, edukacyjnej czy zawodowej (Merino i in., 2020), co jest zgodne z wynikami badań zawartymi w niniejszym opracowaniu. Hipoteza druga, zakładająca, że resilience będzie moderować związek między orientacją pozytywną a postrzeganymi pozytywnymi zmianami w funkcjonowaniu również została potwierdzona.…”
Section: Dyskusjaunclassified
“…The COVID-19 pandemic, caused by the Severe Acute Respiratory Syndrome Coronavirus Type 2 (SARS-CoV-2), has caused major impacts worldwide [19][20][21][22][23][24][25][26][27][28][29][30][31][32]. It remains to be seen whether these changes are temporary or lasting, taking shape in a new normal [31,33].…”
Section: Introductionmentioning
confidence: 99%